Studies in Insect Parasitism I - III. The effect of different hosts on the physiology, on the development and behaviour and on the sex-ratio of Microbracon gelechiae Ashmead. (Hymenoptera: Braconidae). - Narayanan, E. S.; Subba Rao, B. R. (Contributions to Entomology = Beiträge zur Entomologie, 1955)
(1) The viability of unfertilized eggs is higher than that of the eggs of mated females. - (2) The effect of different hosts on the sex-ratio of Microbracon gelechiae Ashm. is shown. - (3) It is seen that as the degree of superparasitism increases the percentage of males also rises. - (4) The morphology of the spermatheca and the mechanism of the discharge of sperm are described. - (5) The various factors that determine the sex-ratio of a parasite and with particular reference to M. gelechiae are discussed. It is shown that the production of excess males in many cases is the direct effect of inadequate external stimulation of the spermatheca, which depends on host suitability. In gregarious species like M. gelechiae the male sex predominates because of differential mortality resulting from superparasitism. It is evident that the haploid male is less affected by larval starvation, than deploid males and females.The sex-ratio of a parasite is determined by various external and internal influence. The action of the spermatheca in liberating the sperm and the differential mortality during the larval stages are mainly responsible for the ultimate sex-ratio of the parasite.